Disrupting the autocratization sequence: towards democratic resilience. Issue 5 (4th July 2021) - Lührmann, Anna
ABSTRACT: Contemporary autocratization is typically the result of a long sequence of events and gradual processes. How can democratic actors disrupt such autocratization sequences in order to enhance democratic resilience? To address this question, this conclusion presents an ideal-typical autocratization sequence and entry points for democratic resilience. It builds on the findings of this special issue, extant research and a novel descriptive analysis of V-Party data. In the first autocratization stage, citizens' discontent with democratic institutions and parties mounts. Remedies lie in the areas of a better supply of democratic parties and processes as well as in civic education. During the second stage, anti-pluralists – actors lacking commitment to democratic norms – exploit and fuel such discontent to rise to power. In order to avoid the pitfalls of common response strategies, this article suggests "critical engagement", which balances targeted sanctions against radicals with attempts to persuade moderate followers; and has the aim of decreasing the salience of anti-pluralists' narratives by means of democratic (voter) mobilization. Thirdly, once autocratization begins, weak accountability mechanisms and opposition actors enable democratic breakdown. Thus, resilient institutions and a united and creative opposition are the last line of democratic defense.